Barriers and facilitators in the provision of palliative care in adult intensive care units: a scoping review - Effendy, Christantie; Yodang, Yodang; Amalia, Sarah; Rochmawati, Erna (The Korean Society of Critical Care Medicine, 2022)
The provision of palliative care in the intensive care unit (ICU) is increasing. While some scholars have suggested the goals of palliative care to not be aligned with the ICU, some evidence show benefits of the integration. This review aimed to explore and synthesize research that identified barriers and facilitators in the provision of palliative care in the ICU. This review utilized Preferred Reporting Items for Systematic Reviews and Meta-Analyses Scoping Review guidelines based on population, concept, and context. We searched for eligible studies in five electronic databases (Scopus, PubMed, ProQuest, Science Direct, and Sage) and included studies on the provision of palliative care (concept) in the ICU (context) that were published in English between 2005–2021. We describe the provision of palliative care in terms of barriers and facilitators. We also describe the study design and context. A total of 14 papers was included. Several barriers and facilitators in providing palliative care in the ICU were identified and include lack of capabilities, family boundaries, practical issues, cultural differences. Facilitators of the provision of palliative care in an ICU include greater experience and supportive behaviors, i.e., collaborations between health care professionals. This scoping review demonstrates the breadth of barriers and facilitators of palliative care in the ICU. Hospital management can consider findings of the current review to better integrate palliative care in the ICU.